2001
DOI: 10.1002/1098-2345(200101)53:1<1::aid-ajp1>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic history of sifakas (Propithecus: Lemuriformes) derived from mtDNA sequences

Abstract: The sifakas (Propithecus) include three species containing up to 10 described subspecies, whose evolutionary relationships remain contentious. In particular, it is unclear whether P. verreauxi deckeni and P.v. coronatus populations are differentiated at the subspecific level. Furthermore, the taxonomic status of the recently discovered P. tattersalli and its phylogenetic position also require further examination. About 2,400 bp of mitochondrial DNA sequence data from part of the COIII gene, together with compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 28 publications
3
47
0
Order By: Relevance
“…The origins of most samples have been reported (12)(13)(14)(15)(16)(17). Two bush babies (Otolemur crassicaudatus and Galago senegalensis) were sequenced to provide an outgroup.…”
Section: Methodsmentioning
confidence: 99%
“…The origins of most samples have been reported (12)(13)(14)(15)(16)(17). Two bush babies (Otolemur crassicaudatus and Galago senegalensis) were sequenced to provide an outgroup.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the study of mtDNA by Pastorini et al (2001aPastorini et al ( , 2003 grouped Propithecus tattersalli with the P. verreauxi group, and even, assuming a version of the Genetic Species Concept, called into question whether or not it deserved specific status. Independent analyses of mitochondrial DNA (Mayor et al 2004;Pastorini et al 2001a) and clusters based on morphological characteristics (Mayor et al 2004) have confirmed the close link between Propithecus tattersalli and P. coquereli. The karyotype separates it from all other forms of Propithecus (Mayor et al 2004;Rumpler et al 2004).…”
Section: Family Indriidae Burnett 1828mentioning
confidence: 99%
“…He also promoted the former P. v. verreauxi, P. v. coquereli, and P. v. deckenii to full species, with the latter embracing the subspecies P. d. deckenii and P. d. coronatus. Pastorini, et al 67 then used mtDNA distances to restore the traditional two-species division, to suggest that the karyotypically distinct P. tattersalli paired with P. v. coquereli, and to conclude that subspecific distinction between P. v. coronatus and P. v. deckenii is not warranted. Thalmann et al 68 disagreed, presenting persuasive morphological and distributional evidence for distinguishing P. v. coronatus from P. v. deckenii.…”
Section: Genus Propithecusmentioning
confidence: 99%